Pengaruh Fraud Theory dan Kepemilikan Manajerial Terhadap Fraudulent Financial Satetement - Jasmine Eirene; Prita Karina Diandra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to examine the influence of pressure, opportunity, rationalization, and managerial ownership on fraudulent financial statements, measured using the M-Score. Pressure is proxied by financial stability, opportunity by the nature of industry, and rationalization by TATA, which reflects the tendency for accrual-based manipulation. The study employs secondary data from companies in the energy and basic material sectors categorized as mining industries and listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The research population consists of 72 companies, and the analysis is conducted using panel data regression with EViews 13. The results indicate that pressure, opportunity, and rationalization have a positive and significant effect on fraudulent financial statements. These findings suggest that unstable financial conditions, industry characteristics that create opportunities for manipulation, and aggressive accrual practices increase the likelihood of financial statement fraud. Meanwhile, managerial ownership shows no significant effect, implying that managerial shareholding is not sufficient to reduce the risk of fraud. This study contributes to the literature by highlighting the key drivers of fraudulent reporting and emphasizes the need for stronger governance mechanisms and fraud-risk oversight within mining companies that face high operational.